Monetary policy of central banks and its effect on private and public indebtedness - Danišková, Alexandra; Brůna, Karel, 1973-; Šímová, Kateřina; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
This thesis investigates the relationship between central bank monetary policy – more specifically the central bank policy interest rate and indebtedness within the public and private sectors across different countries. Utilizing an Autoregressive Distributed Lag (ARDL) approach, this study provides a comparative analysis of the impact of policy rates on debt dynamics in the Czech Republic, Germany, and Greece. Moreover, the effect of the real GDP change was added as another explanatory variable due to the inherent impact to the debt/GDP ratio. The research findings differ across the countries but also across the public and private sector within the same countries. In general, the results support the inverse effect of the real GDP change on the debt/GDP ratio. The effect of the central bank policy interest rate is, on the other hand less significant and varies not only in the strength but also the sign of the coefficient.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses